Reduced chatter bang-bang-like SMC flux and speed control of induction motor - Mohamed, H.A.F.; Lau, E.L.; Moghavvemi, M.; Yang, S.S. (2008)
This paper presents the design and implementation of a Bang-Bang-like Sliding Mode Control (SMC) methodology to control the flux and speed of an induction motor. The proposed control structure uses a fuzzy logic membership function to combine the bang-bang controller with a PI controller to reduce the chatter created by the switching control input. In this strategy, SMC is responsive during transient state while PI control becomes fully active in the steady state area. This will ensure that the final controller will avoid the switching controller's inherent chattering problem in steady state and PI's overshoot, long settling time and rise time problems. The combination of both control strategies through fuzzy logic provides a mean to create a hybrid control strategy. Simulations of the proposed strategy on the flux and speed controllers displayed diminished chatter, overshoot and significant reduction of settling time.